Women as economic actors in the family: The importance of religion and community in Payungi’s women empowerment - Dwi Nugroho; Dharma Setyawan; Dewi Sri Yunita (Center for Islamic Economics and Development Studies [P3EI], 2023)
Purpose – This study aims to examine the important role of religion and the contribution of the community to empower women in building women's capabilities as actors in the family economy.Methodology – This study uses a qualitative method with an ethnographic approach and collects data using observation, interviews, and documentation studies.Findings – This study shows that the contextualization of religious teachings, which are widely discussed in religious forums (Payungi Entrepreneurial Pesantren), and the contribution of the community in the actualization of ideas in women's empowerment can change the negative stigma of women and encourage women to become economic actors in the family through women's entrepreneurial activities.Implications – Religion and community can be optimized to encourage women to build capabilities and respond to various forms of inequality. Their existence in empowering women contributes to shaping the character of women entrepreneurs by prioritizing religious and collectivity values.Originality – This study completes the puzzle of previous research deficiencies by revealing phenomena in women's empowerment built from religious spirits and transformative movements produced by the community.